• Shuffle
Toggle On
Toggle Off
• Alphabetize
Toggle On
Toggle Off
• Front First
Toggle On
Toggle Off
• Both Sides
Toggle On
Toggle Off
Toggle On
Toggle Off
Front

### How to study your flashcards.

Right/Left arrow keys: Navigate between flashcards.right arrow keyleft arrow key

Up/Down arrow keys: Flip the card between the front and back.down keyup key

H key: Show hint (3rd side).h key

A key: Read text to speech.a key

Play button

Play button

Progress

1/15

Click to flip

### 15 Cards in this Set

• Front
• Back
 Exponential Rule (with e) y=ke^(f(x)) y'=kf'(x)e^(f(x)) Logarithm Rule y=klogb(f(x)) y'=kf'(x)/(lnb*f(x)) Natural Log y=klnf(x) y'=kf'(x)/f(x) y=sin(f(x)) y'=cos(f(x))*f'(x) y=cos(f(x)) y'=-sin(f(x))*f'(x) y=tan(f(x)) y'=(sec^2(f(x)))*f'(x) y=csc(f(x)) y'=-csc(f(x))cot(f(x))*f'(x) y=sec(f(x)) y'=sec(f(x))tan(f(x))*f'(x) y=cot(f(x)) y'=-csc^2(f(x))*f'(x) y=sin^-1(f(x)) y'=f'(x)/(sqrt(1-f^2(x))) y=cos^-1(f(x)) y'=-f'(x)/(sqrt(1-f^2(x))) y=tan^-1(f(x)) y'=f'(x)/1+f(x)^2 y=csc^-1(f(x)) y'=-f'(x)/(abs(x)(x^2-1)) y=sec^-1(f(x)) y'=f'(x)/abs(x)sqrt(f(x)^2-1) y=cot^-1(f(x)) y'=f'(x)/(1+f^2(x))